2021
DOI: 10.1080/10903127.2021.1939817
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Emergency Medical Dispatch (EMD) Telephone Screening in Identifying COVID-19 Positive Patients

Abstract: BackgroundIn response to the COVID-19 pandemic, Emergency Medical Services (EMS) systems have received guidelines as part of coordinated response efforts aimed at mitigating exposures and ensuring occupational wellbeing, including recommendations of Personal Protective Equipment (PPE) utilization, and modifications of Emergency Medical Dispatch (EMD) caller queries. The aim of the study was to estimate the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of an EMD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…There is a balance to strike between additional workload and gain. Our study, along with those by both Pineo et al [19] and Spangler et al, [20] highlight the significant challenges services face in identifying COVID-19 using telephone and clinical triage. Importantly, these poor PPV during triage reinforce current NHS recommended enhanced PPE approaches during prehospital patient care.…”
Section: Triage Systemssupporting
confidence: 64%
See 1 more Smart Citation
“…There is a balance to strike between additional workload and gain. Our study, along with those by both Pineo et al [19] and Spangler et al, [20] highlight the significant challenges services face in identifying COVID-19 using telephone and clinical triage. Importantly, these poor PPV during triage reinforce current NHS recommended enhanced PPE approaches during prehospital patient care.…”
Section: Triage Systemssupporting
confidence: 64%
“…However, this was slightly lower than in two other recently published, although smaller, studies. The first, a study by Pineo et al, [19] examined the positive predictive value of MPDS Protocol 36 in New York City, USA and determined this to be 24.3% and the second by Spangler et al, [20] a nurse led triage system in Sweden, reported a PPV of 24.7% (in tested patients). It is not known why there is a difference in PPV using the same or similar systems.…”
Section: Triage Systemsmentioning
confidence: 99%
“…According to their findings, initial vital signs (with the exception of body temperature) [ 82 ], prehospital triage tools [ 81 ], and telephone screening processes/surveillance tools used by emergency medical dispatchers [ 46 , 65 , 77 , 80 ] had little to moderate predictive value for the identification of COVID-19 patients and/or death.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrate lower rates of bystander cardiopulmonary resuscitation and public AED usage, which corresponds to lower rates of sustained return of spontaneous circulation (ROSC), lower survival to hospital discharge, and in general, a higher incidence of OHCA during the COVID-19 pandemic compared to prior years [32,34]. Furthermore, EMS agencies have implemented rigorous screening protocols for potential COVID-19 symptoms or known infections in all EMS calls, and new processes have been introduced to ensure that first responders have access to appropriate personal protective equipment (PPE), thereby maximizing their safety during interventions [35,36].…”
Section: Introductionmentioning
confidence: 99%